2015
DOI: 10.4238/2015.march.30.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of casein genes - beta-LGB, DGAT1, GH, and LHR - on milk production and milk composition traits in crossbred Holsteins

Abstract: ABSTRACT. The objectives of this study were to determine the effects of a single gene and composite genotype of the casein gene family, including the beta-lactoglobulin gene (beta-LGB), acyl-CoA: diacylglycerol acyltransferase 1 gene (DGAT1), growth hormone gene (GH), and luteinizing hormone receptor gene (LHR) on milk yield, milk composition, the percentage of fat, protein, solids-not-fat, and total solid in crossbred Holsteins. A total of 231 crossbred Holstein cows were examined for the study. The genotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
1
18
0
10
Order By: Relevance
“…Metin Kiyici with coauthors (Metin Kiyici et al, 2019) considers GH gene as one of the promising candidates for assessing the potential milk production of dairy cow. In addition, according to Molee with coauthors (Molee et al, 2015), the LGB + GH gene model may be the most suitable for breeding to improve the milk production of cows. Sabour and Lin (Sabour & Lin, 1996), in turn, found that the V allele of the GH gene was preferable in terms of increasing the milk yield obtained from cows.…”
Section: 1discussionmentioning
confidence: 99%
“…Metin Kiyici with coauthors (Metin Kiyici et al, 2019) considers GH gene as one of the promising candidates for assessing the potential milk production of dairy cow. In addition, according to Molee with coauthors (Molee et al, 2015), the LGB + GH gene model may be the most suitable for breeding to improve the milk production of cows. Sabour and Lin (Sabour & Lin, 1996), in turn, found that the V allele of the GH gene was preferable in terms of increasing the milk yield obtained from cows.…”
Section: 1discussionmentioning
confidence: 99%
“…Some authors reported the possibility of using milk protein as a polymorphic genetic marker (Eenennaam and Medrano, 1991;Chung et al, 1996;Kaygisiz and Dogan, 1999;Ikonen et al, 1999;Cardak, 2005;Alipanah et al, 2008;Heck et al, 2009;Mohammadi et al, 2013;Djedovic et al, 2015;Dyman et al, 2015). However, these relationships were reported to be non-significant by other researchers (Sekerden et al, 1999;Jusczak et al, 2001;Micinski et al, 2006;Ozdemir and Dogru, 2007;Gurcan, 2011;Dogru, 2015a;Molee et al, 2015).…”
Section: Introductionmentioning
confidence: 90%
“…However, when analyses were performed according to the recessive model, the dairy subgroup AA vs. AB + BB genotype mean difference was found to be statistically significant (P <0.05) and was observed to provide advantages in favor of AA (Table 1). In some individual studies performed previously, it was reported that CSN3 AA and AB genotypes had superiority (Cardak, 2005;Pawelska-Goral et al, 2008;Bartonova et al, 2012;Molee et al, 2015). Some researchers reported that daily milk yield means were not significant among CSN3 genotypes (Dogru, 1994;Ozdemir and Dogru, 2005;Gurcan, 2011).…”
Section: Analysis Of Csn3 Genotypesmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies of Romanian Simmental cattle have suggested an association between LGB genotypes and milk yield [17]. Molee et al (2015) [22] have shown that the specific combination of genotypes at the GH (growth hormone) and LGB loci can affect milk production and protein content and can therefore serve as a useful genetic marker in selection programs for crossbred Holstein cattle. Finally, it was suggested that the LGB gene may also be important in the context of milk processing technology, as particular genotypes are significantly associated with rennet coagulation time in Brown Swiss cows [23].…”
Section: Introductionmentioning
confidence: 99%